Monthly precipitations over semi‐arid basins in Northern Africa: Homogenization and trends. (24th April 2020) - Abahous, Houria; Guijarro, Jose A.; Sifeddine, Abdelfettah; Chehbouni, Abdelghani; Ouazar, Driss; Bouchaou, Lhoussaine
Abstract: Long‐term and high quality observed climate data are required to analyse with reduced uncertainty temporal and spatial climate variability. The aim of this work is the quality control, the reconstruction and homogenization of monthly precipitation observed in semi‐arid basins within Souss‐Massa region in North Africa during the period 1933–2010. Data recorded in local meteorological stations underwent a neighbour‐based homogenization algorithm. We apply Mann‐Kendall test and Sen's method to raw and homogenized time series to calculate trends and their magnitude. The greatest variation in data properties is highlighted for the trend analysis where the homogenization process allows the detection of a higher number of the statistically significant negative trend with 95 and 99% confidence levels. Abstract : Observed monthly precipitation recorded in an important number of meteorological stations located in semi‐arid basins Northern Africa is presenting discontinuities during the period 1933–2010. First, a control of quality followed by data imputation and finally iterative homogenization process (Guijarro, User's Guide to Climatol, 2014) are undertaken. Trend analysis is comparing results before and after homogenization.